WACANA PERADILAN ELEKTRONIK DALAM PROSES EKSEKUSI PUTUSAN PENGADILAN DI LINGKUNGAN PERADILAN TATA USAHA NEGARA - Muhammad Adiguna Bimasakti (Jurnal Hukum Peratun, 2022)
In the past, the litigation process in court was carried out manually from registration of cases to the reading of court’ decision. With the promulgation of Supreme Court Regulation No. 1 of 2019 concerning the Administration of Cases and Hearing in Electronic Courts (PERMA No. 1 of 2019), the paradigm regarding judiciary process has shifted towards electronic justice. In the sense that from registration of cases, the adjudication stage (trial in court) and the reading of court decisions is carried out electronically with the e-court application. However, this regulation did not reach the post-adjudication administrative process, at the stage of execution of the decision. For this reason, this paper was made to look at the potential for the implementation of administration of the execution of court decisions, especially in the administrative court, through the hierarchical execution process using the e-court application. The results of the study indicate that the administrative process of the execution of administrative court decisions can be carried out through the e-court application by changing the e-litigation paradigm, namely the change in PERMA no. 1 of 2019. The e-litigation paradigm in this regulation must also be expanded into e-judiciary (holistic electronic judiciary) so that the execution stage can be carried out electronically.